Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.3390/ijerph15040585
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Algae Age and Population on the Response to TiO2 Nanoparticles

Abstract: This work shows the influence of algae age (at the time of the exposure) and the initial algae population on the response of green algae Raphidocelis subcapitata to titanium dioxide nanoparticles (TiO2 NPs). The different algae age was obtained by changes in flow rate of continually stirred tank reactors prior to NP exposure. Increased algae age led to a decreased growth, variations in chlorophyll content, and an increased lipid peroxidation. Increased initial algae population (0.3−4.2 × 106 cells/mL) at a con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 62 publications
(70 reference statements)
0
5
0
Order By: Relevance
“…Based on the transient and disproportionate biomass-dependent nature of this response, we have hypothesized that this feature is unlikely to be caused directly by degradation of biomass or increased encounter rates but instead may represent a defense response that is nonlinearly amplified by denser cell populations. The possibility that algae respond to stressful stimuli in a population-dependent manner, as has been observed in the literature to abiotic stress ( 45 ), indicates that gas analysis as a diagnostic method will likely require multiple data types to contextualize the overall SoH of the algal crop. Second, we observed that overall signal changes occur earlier when infection occurs at a higher initial biomass density ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the transient and disproportionate biomass-dependent nature of this response, we have hypothesized that this feature is unlikely to be caused directly by degradation of biomass or increased encounter rates but instead may represent a defense response that is nonlinearly amplified by denser cell populations. The possibility that algae respond to stressful stimuli in a population-dependent manner, as has been observed in the literature to abiotic stress ( 45 ), indicates that gas analysis as a diagnostic method will likely require multiple data types to contextualize the overall SoH of the algal crop. Second, we observed that overall signal changes occur earlier when infection occurs at a higher initial biomass density ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Photosynthesis is one of the most important metabolic activities of algae, and chlorophyll is its main pigment. Studies have shown that when algae are stressed by the outside world, the algae cell chlorophyll a will also be affected(Alahverdi &Savabieasfahani 2012, Metzler et al 2018, Patil et al 2017. In this study, with the increase of the concentration of particulate matter, the chlorophyll a content of Microcystis os-aquae gradually decreased, that is, the higher the concentration of particulate matter, the stronger the attenuation of light by suspended particles.…”
Section: Effects Of Suspended Particles In Water On Lipid Peroxidatio...mentioning
confidence: 48%
“…Photosynthesis is one of the most important metabolic activities of algae, and chlorophyll is its main pigment. Studies have shown that when algae are stressed by the outside world, the algae cell chlorophyll a will also be affected (Alahverdi &Savabieasfahani 2012, Metzler et al 2018, Patil et al 2017. In this study, with the increase of the concentration of particulate matter, the chlorophyll a content of Microcystis os-aquae gradually decreased, that is, the higher the concentration of particulate matter, the stronger the attenuation of light by suspended particles.…”
Section: Effects Of Suspended Particles In Water On Lipid Peroxidation and Antioxidant Capacity Of Microcystis Osaquaementioning
confidence: 57%